Nicholas Georgiadis Book review - Woodcock, Sarah (Dance Books Ltd., Alton,Hampshire (UK), 2005)
PALABRAS CLAVE: Nicholas Georgiadis, dance and painters.
Nicholas Georgiadis. Evgenia Georgiadis, edited by Robert Oresko, Olkos E.P.E., Ekdoseis, 2004.